CO-SPACES: FUTURE TOOL TO FOSTER CREATIVITY IN LEARNERS - Rasna Sehrawat. T.P. Sarma (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2022)
In the current scenario, the most applied tool in pedagogy for student engagement and curriculum dissemination is technology, be it transaction through online mode or use of various e-tools for transaction and assessment procedures. Moving ahead with it, immersive technologies like augmented reality and virtual reality are also now being explored and blended by the teachers in their teaching learning processes. These techniques would enhance immersive learning in the students through a simulated environment providing them a real experience of even abstract concepts. One of the tools of immersive learning discussed in this paper is Co Spaces. It is an incredible tool as experienced by the researcher firsthand, which provides endless possibilities to the teachers and students to create 3-D world for the students and grab experience in 360-degree transition as well. This paper specifically deals with the process of using CoSpaces as content development tool for K-12 education. Keywords: Digital Technology, Immersive Technologies, Augmented Reality, Cospaces as augmented reality tool, Pedagogical Practices